The role of the Muslim family in the spiritual education of children in light of the challenges of the Internet - Ali, Siteljeel Ibrahim (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the role of the Muslim family in the spiritual education of children in light of the challenges of the Internet, through the development of the Islamic faith in the hearts of children and recommending it to various worships, and to reveal the challenges facing the Muslim family in the spiritual education of children through this network, and to identify the role of the Muslim family in facing these challenges, To achieve these objectives, the study used the descriptive method in collecting and analyzing information, and the results of the study resulted in: that the Muslim family has a major role in the spiritual education of children in light of the challenges of the Internet, and that the success of the role of the family in this education depends on its general culture and Islamic culture, and that the family follows some steps and measures that help it in the spiritual education of children in light of these challenges, and recommended the study, educational institutions for the Muslim family and the development of programs and plans to solve the problems facing the Muslim family in the spiritual education of the Muslim family in the light of these challenges, and recommended the study, educational courses for the Muslim family and the development of programs and plans to solve the problems facing the Muslim family in the spiritual education of the Muslim family. For children, the general education curriculum includes a special course on how to use the Internet, conducting modern educational studies and articles related to the spiritual education of children in light of the challenges of the Internet.
Keywords: Muslim Family; Spiritual Education; Internet